Thermal-hydraulically calculation for the Dalat nuclear research reactor - Khang, Ngo Phu (Vietnam Journal of Mechanics, 1991)
This paper concerns with thermal-hydraulically calculation for the core domain of the Dalat nuclear reactor in the nominal regime of works. On the base of this calculation some conclusions. On thermal safely of the reactor are conducted.